Use of burnt clay aggregate as phase change material carrier to improve thermal properties of concrete panel. (December 2019) - Pongsopha, Phattharachai; Sukontasukkul, Piti; Phoo-ngernkham, Tanakorn; Imjai, Thanongsak; Jamsawang, Pitthaya; Chindaprasirt, Prinya
Abstract: In this research, the thermal properties of paraffin-impregnated burnt clay aggregate (PIA) concrete were studied. Paraffin was used as a phase change material (PCM) carrier and was incorporated into the burnt clay aggregates using heat and pressure. The compressive and flexural strengths of the concretes and the thermal insulation of the concrete panels were tested. The results of these tests revealed that the strengths and thermal insulation of the standard burnt clay aggregate concrete were improved with the use of PIA. The panels with PIA required more time to reach peak temperature and exhibited a larger drop in peak temperature relative to the control panel without PIA.